2009
DOI: 10.1002/ijc.24651
|View full text |Cite
|
Sign up to set email alerts
|

HER3 is required for the maintenance of neuregulin‐dependent and ‐independent attributes of malignant progression in prostate cancer cells

Abstract: HER3 (ERBB3) is a catalytically inactive pseudokinase of the HER receptor tyrosine kinase family, frequently overexpressed in prostate and other cancers. Aberrant expression and mutations of 2 other members of the family, EGFR and HER2, are key carcinogenic events in several types of tumors, and both are wellvalidated therapeutic targets. In this study, we show that HER3 is required to maintain the motile and invasive phenotypes of prostate (DU-145) and breast (MCF-7) cancer cells in response to the HER3 ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…These results suggest a relative role for neuregulin-1 in promoting the cell survival, probably because other ligands, like neuregulin-2, may be involved in activating the signaling through HER3 in these cells. In addition, a recent work describe that HER3 may be activated in a neuregulin-1 independent manner in DU145 cells (22).…”
Section: Her Receptors Activation and Downstream Signaling Activity Imentioning
confidence: 97%
See 1 more Smart Citation
“…These results suggest a relative role for neuregulin-1 in promoting the cell survival, probably because other ligands, like neuregulin-2, may be involved in activating the signaling through HER3 in these cells. In addition, a recent work describe that HER3 may be activated in a neuregulin-1 independent manner in DU145 cells (22).…”
Section: Her Receptors Activation and Downstream Signaling Activity Imentioning
confidence: 97%
“…However, the marked differences in the specificity and clinical efficiency of the HER inhibitors in different carcinomas as well as the development of resistances have limited the efficacy of these drugs (18,19). In PCa, EGFR, HER2 and HER3 expression levels are increased as the disease progresses from localized to metastasic and to the androgen-independent state and these receptors have long been implicated in the survival of androgen-independent prostate cancer cells (20)(21)(22)(23). Thus, the HER family members have been considered as potential therapeutic targets in prostate cancer.…”
Section: Androgen-independent Prostate Cancer Cells Circumvent Egfr Imentioning
confidence: 99%
“…2 and results in a protein of about 180 KDa (10)(11)(12). HER3 overexpression was illustrated in a wide range of cancers including those of breast, ovary, lung, and prostate, as well as melanoma (13)(14)(15)(16). This genetic feature has been correlated with poor prognosis in most of the cases (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…We postulate that pancreatic cancer cellular proliferation is directly affected by the level of ErbB3 expression. While several groups have shown that silencing of ErbB3 expression diminishes basal cell proliferation, 15,16,27 our study is the first attempt to demonstrate increased pancreatic cancer cell growth with the introduction of exogenous ErbB3. ErbB3 is closely associated with PI3K-AKT signaling 8 and the potency of this receptor signaling cascade is only now being realized.…”
Section: Discussionmentioning
confidence: 74%
“…Traditionally, it was thought that ErbB3 played a moderator role in cellular proliferation acting as a simple scaffolding partner for the other signaling receptors, such as EGFR and ErbB2. 5 In prostate cancer, 27 lung cancer 28 and melanoma, 29 it has been speculated that the EGFR-ErbB3 heterodimer contributes to tumorigenesis, and here, utilizing pancreatic adenocarcinoma, we identified ErbB3 as the critical, rate-limiting component in EGFR-dependent cellular proliferation. We postulate that pancreatic cancer cellular proliferation is directly affected by the level of ErbB3 expression.…”
Section: Discussionmentioning
confidence: 77%